Encyclopedia of African American history, 1619-1895 : from the colonial period to the age of Frederick Douglass - Finkelman, Paul, 1949- (New York : Oxford University Press, 2006)
In nearly 700 entries, this set documents the full range of the African American experience during the period from the arrival of the first slave ship to the death of Frederick Douglass, and shows how all aspects of American culture, history, and national identity have been profoundly influenced by the experience of African Americans.
v. 1. A-E -- v. 2. F-Q -- v. 3. R-W.
Includes bibliographical references and index.
Keywords: African Americans -- History -- Encyclopedias; African Americans -- History -- To 1863 -- Encyclopedias; African Americans -- History -- 1863-1877 -- Encyclopedias